Designing a fixed cost model for aftermarket at a surveillace company - Almér, Lovisa; Göthberg, Hugo (My University, 2020)
Introduction - For companies in general, Aftermarket is an important business area for achieving longtime success. The Case Company, where the thesis was conducted at, desired to improve their operations within their Aftermarket division. The Repair Process at The Case Company is time-consuming and complex with their current way of operating. The lead times are affected due to the following four aspects; products, customers, subcontractors, and in-house operations. Aim - The aim of the thesis consisted of fulfilling three parts; (1) an analysis of all costs related to establishing quotation, (2) defining a fixed cost model for Aftermarket, and (3) suggesting an implementation of such a fixed cost model. Methods - To obtain the best result, a mixed-method approach, combining qualitative and quantitative methods, was used during the thesis. Several interviews were conducted to receive information regarding how quotations are established. Regarding the fixed cost model, interviews, focus groups, observations and a Beta Distribution Estimation was used to develop the model. As a complement to the various methods a literature review was conducted, and for the implementation of the model it can be regarded as the primary source for the evolution of the process. Further, ethical considerations were an important aspect of the thesis since The Case Company operates within the military field. Results - Found was that a quotation, with the current process, consists of four parts; Fault Verification Process & Shipment, Reparation In-House, Fault verification Process for Sub-Contractors, and Reparation Sub-Contractor. The fixed cost model was developed with the help of a Process Information Database. The implementation process that was established for the fixed cost model is based on an eighth step approach. Conclusion - Overall, the empirical results demonstrate that The Case Company will improve their efficiency in their after-sales service due to a more automatized quotation process. The authors have encountered challenges that have slowed down the process of constructing the fixed cost model. Despite that, the authors believe that the fixed cost model, in a future state, will contribute to The Case Company’s longtime success.
Keywords: Fixed cost model; Quotation; Aftermarket; Beta Distribution; Estimation,; Repair Process,; Reduced lead time,; Process Information Database (PID).